Generation of shock-free pressure waves in shaped resonators by boundary driving - Luo, C. (2012)
Investigation of high amplitude pressure oscillations generated by boundary driving in shaped resonators has been carried out both theoretically and experimentally. In the theoretical modeling, the acoustic resonance in an axisymmetric resonator is studied by the Galerkin method. The resonator is exponentially expanded and the boundary driving is provided by a piston at one end. The pressure wave forms, amplitudes, resonance frequencies, and ratio of pressures at the two ends of the resonator are calculated for various expansion flare constants and driving strengths. These results are partially compared with those generated by shaking the resonator. They are also verified in the experiment, in which an exponentially expanded resonator is connected to a speaker box functioning as the piston. The experiment is further extended to a horn-shaped resonator with a rectangular cross section. The boundary driving in this case is generated by a circular piezoelectric disk, which forms one sidewall of the resonator cavity. The characteristics of axisymmetric resonators, such as the resonance frequency and amplitude ratio of pressures at the two ends, are observed in this low aspect ratio rectangular resonator with the sidewall driving.